High‐Speed Electron Flows in the Earth Magnetotail - Huijie Liu; Wenya Li; Binbin Tang; Cecilia Norgren; Kaijun Liu; Yuri V. Khotyaintsev; Daniel Graham; Tongkuai Li; Chongle Zhang; Andris Vaivads; Shan Wang; Jiansen He; et al. (AGU Advances)
Abstract High‐speed electron flows (HSEFs) play a crucial role in the energy dissipation and conversion processes within the terrestrial magnetosphere and can drive various types of plasma waves and instabilities, affecting the electron‐scale dynamics. The existence, spatial distribution, and general properties of HSEFs in the Earth magnetotail are still unknown. In this study, we conduct a comprehensive survey of HSEFs in the Earth magnetotail, utilizing NASA's Magnetospheric Multiscale (MMS) mission observations from 2017 to 2021. A total of 642 events characterized by electron bulk speeds exceeding 5,000 km/s are identified. The main statistical properties are: (a) The duration of almost all HSEFs are less than 4 s, and the average duration is 0.74 s. (b) HSEFs exhibit a strong dawn‐dusk (30%–70%) asymmetry. (c) 39.6%, 29.0%, and 31.4% of the events are located in the plasma sheet, plasma sheet boundary layer (PSBL), and lobe region, respectively. (d) In the plasma sheet, HSEFs have arbitrary moving directions regarding the ambient magnetic field, and the events near the neutral line predominantly move along the same direction as the ion outflows, indicating outflow electrons generated by magnetic reconnection. (e) HSEFs in the PSBL and lobe mainly move along the ambient magnetic field, and 70% of HSEFs in the PSBL exhibit features of reconnection inflow. The HSEFs in lobe regions may locate near the reconnection electron edges. Our study reveals that the HSEFs in magnetotail are closely associated with magnetic reconnection, and the statistical results deepen the understanding of HSEF fundamental properties in collisionless plasma.